Investigating the Dynamic Relationship between Exercise and Cardiovascular Disease Risk Reduction - Muhammad Talha Mumtaz, Shanaiz Khan, Usama Ikram, Mohammad Mustafa Farooq Khan, Maliha Aslam Khan, Ali Salman (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to investigate the dynamic relationship between exercise and cardiovascular disease (CVD) risk reduction. Methodology; in this cross sectional survey sample of 500 patients from different hospitals of Lahore was included in the study between October 2021 and February 2022. Participants who exercised at least three times a week for an average of 30 minutes or more were considered as physically active. Data was entered and analyzed using SPSS 26. Odds ratio were computed. Results: The demographic characteristics of the participants show that 64.2% of the participants were females with a mean age of 46.2 years. The study results suggest that exercise is significantly associated with a lower risk of CVD. Participants who exercised had a 76% lower risk of CVD compared to those who did not exercise. Additionally, the study demonstrated that longer duration and higher frequency of exercise were associated with lower CVD risk. Implication: Assessing the existing professional exercise recommendations for hypertension, Healthcare professionals can use the findings to guide patients on the benefits of exercise and promote a healthy lifestyle. Conclusion: The findings emphasize the importance of regular physical activity for the prevention of CVD. Future research should explore the most effective types of exercises for risk reduction in different sub-groups. We recommend targeted interventions aimed at promoting an active and healthy lifestyle and raising awareness on the importance of exercise for the prevention of CVD. Keywords: Exercise, Cardiovascular, Risk factors, Physical inactive